2016
DOI: 10.1038/srep35234
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived and peritoneal macrophages have different inflammatory response to oxLDL and M1/M2 marker expression – implications for atherosclerosis research

Abstract: Macrophages are heterogeneous and can polarize into specific subsets, e.g. pro-inflammatory M1-like and re-modelling M2-like macrophages. To determine if peritoneal macrophages (PEMs) or bone marrow derived macrophages (BMDMs) resembled aortic macrophages from ApoE−/− mice, their M1/M2 phenotype, inflammatory status, and lipid metabolism signatures were compared. oxLDL accumulation was similar in PEMs and BMDMs. On protein expression level, BMDMs showed an M2-like CD206highCD11clow profile, while cholesterol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 31 publications
4
58
2
Order By: Relevance
“…In contrast to our findings, previous studies have failed to show increase in glucose uptake in resident peritoneal macrophages activated with IFNγ plus TNF (55). This discrepancy can be explained by functional differences between macrophage sources including the magnitude of their responses to pro-inflammatory and anti-inflammatory stimuli (56,57). Macrophages can also be activated by other stimuli including pathogen-associated molecular patterns (PAMPs) such as LPS.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, previous studies have failed to show increase in glucose uptake in resident peritoneal macrophages activated with IFNγ plus TNF (55). This discrepancy can be explained by functional differences between macrophage sources including the magnitude of their responses to pro-inflammatory and anti-inflammatory stimuli (56,57). Macrophages can also be activated by other stimuli including pathogen-associated molecular patterns (PAMPs) such as LPS.…”
Section: Discussioncontrasting
confidence: 99%
“…Measured differences of CD16 + monocytes in human CAD (Ozaki et al., ) and of M2 macrophages in mouse atherosclerosis (our laboratory; also Bisgaard et al., ) support our cohort as being ≥80% powered to reject null hypotheses correctly, with α = 0.05, for both these measures. For the baseline characteristics of the three groups by CAD severity, one‐way ANOVA was used to compare continuous variables, and post hoc testing was performed using Student's unpaired t tests.…”
Section: Methodssupporting
confidence: 76%
“…Primary cultures of BMDMs from indicated mice were prepared as previously described (43). Briefly, bone marrow cells were harvested from the femurs and tibias of mice.…”
Section: Bmdm Preparationmentioning
confidence: 99%
“…1D). Because PMs have been reported to be activated macrophages (43,53), we examined the surface activation markers and CD23 expression in PMs and BMDMs. We found that PMs expressed higher levels of CD86 (M1 phase macrophage marker) and CD23 ( Supplemental Fig.…”
Section: Cd23 Is Necessary For C Albicans-induced Nf-kb Activation Imentioning
confidence: 99%